Pengaruh Financing to Deposit Ratio, Non-Performing Financing, dan Capital Adequacy Ratio terhadap Profitabilitas Bank Aceh Syariah - Maulida, Ulvia; Muliza, Muliza; Fauza, Muflihatul (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2025)
This study aims to determine the effect of Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Capital Adequecy Ratio (CAR) on Profitability proxied by the Return On Assets (ROA) ratio at Bank Aceh Syariah. This study uses quantitative methods with multiple linear regression analysis techniques. Data collection was carried out by accessing bank financial report data through the Bank Aceh Syariah website from the period 2020-2024. Data analysis in this study includes classical assumption test, multiple linear regression test, and hypothesis testing. The findings indicate that FDR and NPF have no effect on Profitability (ROA), while CAR is known to have a significant effect on ROA. Simultaneously, FDR, NPF, and CAR variables have a significant effect on ROA.